The Waqfs Ordinance (1 of 1962) : with rules and up-to-date decisions - Chowdhury, Purnendu Bikash (Chittagong : Anima Chowdhury ; Dhaka : Sole distributor, Book Syndicate, 1988)
With reference to Bangladesh.
Includes index.
Keywords: Election law -- Bangladesh; Contested elections -- Bangladesh